Study of the Fe2CoAl heusler alloy films growth on the R-plane sapphire substrate by scanning probe microscopy. (12th March 2019) - Malikov, I. V.; Fomin, L. A.; Berezin, V. A.; Chernykh, A. V.; Rai, D. P.; Mikhailov, G. M.
Abstract: The grown films of FCA Heusler alloy on the R-plane sapphire with and without the W (001) seed layer were studied using scanning atomic and magnetic force microscopies, supplemented with the results of micromagnetic calculations and measurements of film magnetoresistance. Nonmonotonic dependences of the films' morphological and magnetic properties on their growth temperature caused, as assumed, by the formation of some disordered phase at temperatures of 50 <  T g < 170 °C with biaxial magnetic anisotropy were found. A more ordered phase grew in the temperature range 170 <  T g < 400 °C, in which there was the uniaxial magnetic anisotropy.